A time-varying strategy for urban traffic network control: a fuzzy logic control based on an improved black hole algorithm. (2017) - Khooban, Mohammad Hassan; Liaghat, Alireza
Urban traffic network (UTN) models are usually illustrated by state-charts (CH) and object-diagrams (OD). So, a state space model is usually used to calculate the half-value waiting time of vehicles in UTN with a stabled time control. In this study, a combination of the general type-2 fuzzy logic sets (GT2FLS) and the modified black hole (MBH) algorithm techniques is used in order to control the traffic signal scheduling and phase succession so as to guarantee the smooth flow of traffic with the least waiting time and average queue length. A comparison is made between the results obtained regarding the performance of the proposed model and those of the optimal type-1 fuzzy logic (OT1FL) and conventional type-1 fuzzy logic (CT1FL) controllers, which are the most recent researches in the problem at hand. The simulation results prove the successfulness and effectiveness of the proposed controller.